Vitamin D Level in Postmenopausal Breast Cancer Patients Before and After Adjuvant Chemotherapy and Endocrine Therapy - Barrak F. Al Obeidy; Alya A. Al Zobair; Mohammed A. Hayawi (Medical Journal of Babylon)
Background: Deficiency of vitamin D is associated with the risk of the development of several cancers. Objective: This study aimed to verify the effect of the adjuvant chemotherapy and hormonal therapy on the vitamin D level in breast cancer patients. Materials and Methods: This is a prospective case–control study consisting of 65 postmenopausal patients with breast cancers compared to 40 postmenopausal control women from Nineveh province, vitamin D level was measured at the time of the diagnosis; immediately after the completion of adjuvant chemotherapy and 6 months after completing chemotherapy attending Mosul oncology Hospital during 2017–2019. Results: The present study demonstrated that vitamin D level at the time of diagnosis was lower in patients group compared with the control group. After the completion of adjuvant chemotherapy, the mean value of vitamin D level was significantly lower than the mean value of vitamin D level at the time of diagnosis. Six months after finishing chemotherapy, the value of vitamin D level was slightly recovered but still significantly lower than the mean value of vitamin D level at the time of diagnosis of breast cancer patients. Conclusion: Vitamin D deficiency seems common among breast cancer patients in Nineveh province, which became more prominent after giving chemotherapy.